Advancing Equity in Public Administration: Prioritizing Equality of Outcomes in the COVID‐19 Crisis. Issue 4 (5th October 2020) - Gadson, Danielle N.
Abstract : The destructive and ubiquitous nature of the COVID‐19 pandemic presents a unique and important backdrop upon which to consider the practicality of an equitable approach to contemporary public administration. To minimize or ignore the specialized needs of marginalized populations in the time of COVID‐19 is to prolong the spread of the disease, social restrictions, and the ultimate recovery of the American economy, as those disproportionally impacted are often public‐facing essential workers who cannot stay home and effectively social distance. This commentary discusses the advancement of social equity as an essential component of policy planning in the current pandemic and offers practical administrative strategies for achievement, including heeding the data, dialoguing with community, partners, and taking courageous action. 摘要: 新冠肺炎(COVID‐19)大流行的破坏性与普遍性提供了一个独特且重要的背景, 用于考量当代公共行政的一项公平措施的可行性。在COVID‐19时期对脆弱人群的特殊需求进行最小化或忽视, 则是在延长疾病的扩散、延长居家限制措施的放宽时间、延长美国经济的最终恢复时间, 因为那些特别受疫情影响的人群是面对公众的基层工作人员, 他们不能待在家也无法有效保持社交距离。本篇评论文探讨了在当前大流行中将社会公平的提升作为政策规划的关键部分, 并就达成此事提供了实用的行政策略, 包括留意数据、与社区和合作伙伴进行对话、以及采取果敢行动。 Resumen: La naturaleza destructiva y ubicua de la pandemia COVID‐19 presenta un telón de fondo único e importante sobre el cual considerar la viabilidad de un enfoque equitativo de la administración pública contemporánea. Minimizar o ignorar las necesidades especializadas de las poblaciones vulnerables en el momento del COVID‐19 es prolongar la propagación de la enfermedad, la relajación de las restricciones de permanencia en el hogar y la recuperación final de la economía estadounidense, ya que los afectados de manera desproporcionada son los trabajadores esenciales de cara al público que no pueden quedarse en casa y distancia social efectiva. Este comentario analiza el avance de la equidad social como un componente esencial de la planificación de políticas en la pandemia actual y ofrece estrategias administrativas prácticas para el logro, que incluyen prestar atención a los datos, dialogar con la comunidad, los socios y tomar medidas valientes.